Teachers’ Perspectives on Stimulation Strategies in Teaching Foreign Language to Young Learners: A Qualitative Study - Wahyuni, Sry; Fitriyani, Fitriyani (The Future of Education Journal, 2025)
This study aims to describe teachers’ perspectives on stimulation strategies in teaching foreign language to young learners. The research focuses on how teachers implement various forms of stimulation through media, teaching methods, individualized support, as well as children’s interests and experiences. A qualitative approach with a case study design was employed, involving early childhood education teachers as the primary participants. Data were collected through interviews and observations, and analyzed using thematic analysis. The findings reveal that teachers apply stimulation strategies through the use of visual and concrete media as mediational tools, varied methods and activities as forms of dynamic scaffolding, individual support to address children’s developmental needs, and the integration of children’s interests and experiences as the foundation of learning. The study concludes that teachers’ stimulation strategies are not merely technical actions, but pedagogical processes rooted in social interaction and gradual support.